Systemic candidiasis in critical patients: Risk predictors - Lazo, Víctor (2018)
Candida sp. is the microorganism most frequently involved in fungal infections in critically ill patients. Candidemia is the most common form of invasive candidiasis entering the bloodstream from the gastrointestinal tract and skin. Worldwide candidemia stands out as one of the leading causes of morbidity with significant increases in its incidence and prevalence in recent years. In addition, it raises the costs of hospital care. Although several studies show that early initiation of antifungal treatment improves patients’ prognosis, there are difficulties with existing diagnostic tests, because they do not have an adequate level of sensitivity and optimum performance. For this reason, various clinical indices are currently being used as predictors of invasive candidiasis, such as Ostrosky Candida Score, Candida Score, Pittet Candida Colonization Index, among others, which have a high negative predictive value that allows to recognize patients who do not benefit from an early initiation of an antifungal treatment while the diagnosis is confirmed by laboratory. Antifungal therapy available for the treatment of candidemia in the ICU consists basically of three groups of drugs: azoles, polyenes and echinocandins. Despite the validation of predictors of invasive candidiasis in other countries, it is still unknown which of these would be the most effective for predicting this disease in the region.